Bio-based polyamides and corresponding polymer compositions
By developing a specific semi-aromatic copolyamide, using specific diamine and dicarboxylic acid components, the dimensional instability and mechanical properties of existing thermoplastic resins under wet or wet conditions are solved, and high dimensional stability and good mechanical properties are achieved, which is suitable for the preparation of thermoplastic composite materials.
Patent Information
- Application Number
- CN202380066665.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-09-19
- Publication Date
- 2025-05-02
AI Technical Summary
Existing thermoplastic resins, such as aliphatic polyamides, have high water absorption, resulting in dimensional instability and reduced mechanical properties, making it difficult to meet the requirements for dimensional stability and mechanical properties under wet or wet conditions.
A semiaromatic copolyamide is developed, which is formed by polycondensation reaction of a specific diamine component and a dicarboxylic acid component, specifically including the use of 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine and mixtures thereof, as well as 1,9-nonanediamine, 1,10-decediamine and mixtures thereof, and the molar ratio and component ratio are optimized to obtain suitable melting point, glass transition temperature and bio-based content.
It achieves a wide processing window between 238°C and 300°C, good crystallization speed and high dimensional stability, high biobase content and good water resistance, and is suitable for the preparation of thermoplastic composite materials.
Smart Images

Figure BDA0005314645480000031 
Figure BDA0005314645480000081 
Figure BDA0005314645480000082
Abstract
Description
[0001] This PCT application claims priority to U.S. Patent Application No. 63 / 407853, filed on September 19, 2022, and European Patent Application No. 22201546.3, filed on October 14, 2022, the contents of which are incorporated herein by reference in their entirety for all purposes. If there are any inconsistencies between this PCT application and those two applications that would affect the clarity of terminology or expression, reference should be made only to this PCT application. [Technical field]
[0002] The present invention relates to a bio-based semi-crystalline copolyamide having a combination of thermal properties and being suitable for the preparation of unfilled and fiber-reinforced thermoplastic compounds and composites. [Background of the invention]
[0004] Aliphatic polyamides (such as the well-known PA6 and PA66) are a very popular class of thermoplastic resins because they are easy to process and generally have a high melting point. They also exhibit high heat resistance values, especially when reinforced with fibers or fillers. However, when stored in water, they typically have high water absorption values of up to 9%.
[0005] Aliphatic polyamides cannot be used in many applications where strict requirements on dimensional stability are required (wet or humid conditions also apply). Water absorption changes not only the dimensions, but also the mechanical properties. Water absorption reduces stiffness and strength to a fraction of their original values. However, there are many applications involving mechanical loads in contact with water or ambient moisture that require dimensional stability and require maintenance of mechanical properties.
[0006] Semiaromatic polyamides have been developed to solve these problems. Trogamid T5000 is a commercial amorphous polyamide consisting of terephthalic acid and a mixture of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD) and 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD). This amorphous polyamide exhibits high mechanical strength and high toughness. However, when exposed to temperatures above its Tg = 150°C (dry state) and in the presence of water, the polyamide loses all its mechanical integrity due to a high moisture absorption rate of about 7.5 wt.%.
[0007] US 8,871,862 discloses a copolyamide comprising in reacted form a) 50 to 95 mol % of a first mixture consisting of terephthalic acid and a diamine selected from the group consisting of 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine and 1,12-dodecanediamine, and b) 5 to 50 mol % of a second mixture consisting of terephthalic acid and at least one diamine selected from the group consisting of 2,2,4-trimethylhexamethylenediamine and 2,4,4-trimethylhexamethylenediamine, wherein the mol % values are based on the totality of components a) and b); and up to 5 mol % of units derived from one or more other monomers selected from the group consisting of acids other than terephthalic acid, lactams and aminocarboxylic acids. US 8,871,862 does not disclose the polyamide of the present invention.
[0008] US 4,495,328 describes a semicrystalline polyamide made from a mixture of terephthalic acid and hexamethylenediamine with TMD. The document gives PA6T / TMDT (60 / 40, in mol%) as an example, which has a melting point of 310° C. This polyamide has a high melting point, which limits its processing window, especially for extrusion, where the polyamide needs to stay in the molten phase for an extended period of time.
[0009] US 4,476,280 describes copolyamides made from terephthalic acid, isophthalic acid and adipic acid in combination with fossil-based hexamethylenediamine and TMD. These copolyamides exhibit high moisture absorption.
[0010] US2012 / 095161 (D1) discloses a copolyamide comprising in reacted form: a) 50 to 95 mol% of a first mixture comprising terephthalic acid and a diamine selected from the group consisting of 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine and 1,12-dodecanediamine, and b) 5 to 50 mol% of a second mixture comprising terephthalic acid and at least one diamine selected from the group consisting of 2,2,4-trimethylhexamethylenediamine and 2,4,4-trimethylhexamethylenediamine. D1 discloses only the use of terephthalic acid in examples of the invention. According to embodiments, the copolyamide may contain up to 30 mol%, up to 25 mol%, up to 20 mol%, up to 15 mol%, up to 10 mol%, or up to 5 mol% of units derived from other monomers. D1 more particularly discloses the following examples:
[0011] Table I
[0012]
[0013] For a given Tg, they exhibit a high Tm.
[0014] EP 1795632 (D2) discloses a semiaromatic copolyamide comprising dicarboxylic acid units (1), the dicarboxylic acid units containing at least one first dicarboxylic acid unit selected from the group consisting of terephthalic acid units and isophthalic acid units, wherein the proportion of the first dicarboxylic acid unit is not less than 60% by mole relative to the total dicarboxylic acid units; and (2) diamine units, the diamine units containing at least one first diamine unit selected from the group consisting of 2,2,4-trimethylhexanediamine units, 2,4,4-trimethylhexanediamine units, and 1,6-hexanediamine units and at least one second diamine unit selected from the group consisting of 1,9-nonanediamine units and 2-methyl-1,8-octanediamine units, wherein the total proportion of the first diamine unit and the second diamine unit is not less than 60% by mole relative to the total diamine units. Copolyamides B9 and B10 are based on the following components: Diacid component: terephthalic acid (80 mol%) + isophthalic acid (20 mol%); Diamine component: 2,2,4-trimethylhexanediamine (20 mol%) + 1,9-nonanediamine (40 mol%) + 2-methyl-1,8-octanediamine (40 mol%). D2 does not disclose the diamine component (A) as in the present invention.
[0015] [Technical issues]
[0016] In the field of thermoplastic composites, especially for automotive applications, there is an increasing demand for polymer resins that exhibit a combination of a wide processing window between the melting point (Tm) and the degradation point (Tdeg) of the resin, a good crystallization rate, and a high dimensional stability up to at least 80° C. (in dry and humid conditions). Therefore, the polymer resin needs to exhibit a high heat of fusion, a high glass transition temperature (Tg), and a melting point (Tm) that is high enough to withstand heat but below 300° C. to still exhibit good processability.
[0017] Although having a high Tg is beneficial for heat resistance and maintaining mechanical properties up to high temperatures, resins with easier processability are also sought for the preparation of thermoplastic composites. This explains that, for a given Tg, the resin advantageously exhibits a limited Tm between 238°C and 300°C, preferably between 238°C and 290°C (excluding the 290°C value), and a Tm / Tg ratio that is limited such that, for a given Tg, the Tm is as low as possible within the range defined above.
[0018] Furthermore, polymer resins need to exhibit water resistance, especially dimensional stability in the presence of moisture and resistance to hot water.
[0019] In addition, there is an increasing demand to use polymer resins with a lower environmental footprint. Therefore, polymer resins that exhibit a high biobased content as determined according to ASTM D6866-22 are increasingly sought.
[0020] The polyamide of the present invention is intended to solve these technical problems.
[0021] [Brief Summary of the Invention]
[0022] The present invention relates to a polyamide as disclosed in any one of claims 1 to 37. In particular, the present invention relates to a polyamide as disclosed in Example (E*).
[0023] The invention also relates to a process as disclosed in claim 38 for preparing the polyamide according to the invention.
[0024] The present invention also relates to a thermoplastic composite material as disclosed in any one of claims 39 to 40.
[0025] More precise information and details on these topics are now provided below.
[0026] [General definition]
[0027] These definitions apply to this disclosure.
[0028] wt.% is the percentage by weight. Mol.% is the percentage by mole.
[0029] Unless stated otherwise, the proportions of the recurring units in the polyamide are given in mol % and are relative to the total proportions of the recurring units in the polyamide.
[0030]
[0043] Herein, when a numerical range is indicated, the endpoints of the range are included (even open-ended ranges such as those including "at least" or "at most").
[0031] In the present application, unless otherwise indicated, any specific embodiment or technical feature related to one of the subject matters of the present invention is applicable to and interchangeable with another embodiment or technical feature also related to the subject matter and disclosed elsewhere in the present application.
[0032] The proportion of diamines in the diamine component (A) is based on the total amount of diamines in the diamine component (A). The proportion of carboxylic diacids in the dicarboxylic acid component (B) is based on the total amount of dicarboxylic acids in the dicarboxylic acid component (B). [Specific implementation method]
[0033] The present invention relates to a semiaromatic copolyamide (PA) comprising repeating units (R) formed by polycondensation of a diamine component (A) and a dicarboxylic acid component (B). PA),in:
[0034] - the diamine component (A) comprises, consists essentially of, or consists of:
[0035] a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and
[0036] b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof;
[0037] wherein the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 5 / 95 and 47 / 53, and wherein the proportion of DA2 in the diamine component (A) is greater than or equal to 53.0 mol % (≥53.0 mol %), based on the total amount of diamines in the diamine component (A);
[0038] - the dicarboxylic acid component (B) comprises, consists essentially of or consists of:
[0039] a) between 70.0 and 95.0 mol.% of terephthalic acid;
[0040] b) between 5.0 (excluding this value) and 30.0 mol.% of diacids (DI) selected from the group consisting of isophthalic acid, adipic acid (AA), azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, 1,4-cyclohexanedicarboxylic acid (CHDA) and mixtures thereof;
[0041] These proportions in mol % are based on the total amount of diacids in the dicarboxylic acid component (B).
[0042] The polyamide (PA) of the present invention is formed by the polycondensation of a diamine component (A) and a dicarboxylic acid component (B). The reaction is based on the condensation of a diamine and a dicarboxylic acid, wherein an amide bond is formed. A person skilled in the art will then understand that the proportion of -NH2 from the diamine component (A) and the proportion of -COOH from the dicarboxylic acid component (B) are substantially equimolar. The ratio -NH2 / COOH may be comprised between 0.9 and 1.1, preferentially between 0.95 and 1.05, even more preferentially between 0.98 and 1.02.
[0043] The repeating units of polyamide (PA) typically consist essentially of the repeating units (R PA). Therefore, the present invention also relates to a semi-aromatic copolyamide (PA), the repeating units of which are repeating units (R) formed by the polycondensation of a diamine component (A) and a dicarboxylic acid component (B). PA ),in:
[0044] - the diamine component (A) comprises, consists essentially of, or consists of:
[0045] a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and
[0046] b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof;
[0047] wherein the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 5 / 95 and 47 / 53, and wherein the proportion of DA2 in the diamine component (A) is greater than or equal to 53.0 mol % (≥53.0 mol %), based on the total amount of diamines in the diamine component (A);
[0048] - the dicarboxylic acid component (B) comprises, consists essentially of or consists of:
[0049] a) between 70.0 and 95.0 mol.% of terephthalic acid;
[0050] b) between 5.0 (excluding this value) and 30.0 mol.% of diacids (DI) selected from the group consisting of isophthalic acid, adipic acid (AA), azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, 1,4-cyclohexanedicarboxylic acid (CHDA) and mixtures thereof;
[0051] These proportions in mol % are based on the total amount of diacids in the dicarboxylic acid component (B).
[0052] Further details regarding the diamine component (A) and the dicarboxylic acid component (B) are provided below.
[0053] Diamine component (A)
[0054] The diamine component (A) comprises, consists of, or consists essentially of a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD), and mixtures thereof; and a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof.
[0055] DA2 is the main or predominant diamine in the diamine component (A). The proportion of DA2 is greater than or equal to 53.0 mol % (≥53.0 mol %), based on the total amount of diamines in the diamine component (A). The proportion of DA2 is more particularly between 53.0 and 95.0 mol %, based on the total amount of diamines in the diamine component (A). The proportion may more particularly be between 60.0 and 95.0 mol %.
[0056] According to an embodiment, the diamine component (A) comprises: a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10) and mixtures thereof. According to this embodiment, the diamine component (A) may comprise 2-methyl-1,8-octanediamine (MODA), provided that the proportion of MODA in the diamine component (A) is less than and equal to 10.0 mol% (≤10.0 mol%), preferably less than and equal to 5.0 mol% (≤5.0 mol%), the proportion in mol% being based on the total amount of diamines in the diamine component (A).
[0057] According to another embodiment, the diamine component (A) consists essentially of or consists of the first diamine (DA1) and the second diamine (DA2).
[0058] The expression "essentially consists of" means that in the context of the present invention in relation to the diamine component, the diamine component (A) comprises DA1 and DA2 and may also comprise up to 2.0 mol%, preferably up to 1.0 mol%, even more preferably up to 0.5 mol% of another diamine, the proportion in mol%, based on the total amount of diamines in the diamine component (A). In other words, the diamine component (A) consists of DA1, DA2 and up to 2.0 mol%, preferably up to 1.0 mol%, even more preferably up to 0.5 mol%, the proportion in mol%, based on the total amount of diamines in the diamine component (A), of at least one diamine other than DA1 and DA2.
[0059] DA1 is selected from the group consisting of 2,2,4-TMD, 2,4,4-TMD and mixtures thereof. 2,2,4-TMD is a diamine having the formula:
[0060]
[0061] 2,4,4-TMD is a diamine having the formula:
[0062]
[0063] DA1 is conveniently a combination of 2,2,4-TMD and 2,4,4-TMD.
[0064] DA2 is selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof.
[0065] DA2 preferably comprises organic carbon of renewable origin as determined according to ASTM D6866-20.
[0066] DA2 is preferably biobased. The term "biobased" as applied to a compound means that the compound is made from materials containing carbon from a renewable source, derived from living or once living organisms, excluding materials embedded in geological formations and / or petrified, such as petroleum-based materials.
[0067] According to embodiment (E1), DA2 is 1,9-nonanediamine. 1,9-nonanediamine is preferably bio-based (see also below), so that the polyamide (PA) exhibits a high bio-based content.
[0068] According to an advantageous embodiment (E2), DA2 is 1,10-decanediamine. 1,10-Decanediamine is preferably bio-based (see also below), so that the polyamide (PA) exhibits a high bio-based content.
[0069] Molar ratio DA1 / DA2
[0070] In the context of the present disclosure, the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 5 / 95 and 47 / 53. The molar ratio may more particularly be:
[0071] - between 5 / 95 and 40 / 60; or
[0072] - between 15 / 85 and 47 / 53; or
[0073] - between 15 / 85 and 37 / 63; or
[0074] - between 18 / 82 and 47 / 53; or
[0075] - between 8 / 92 and 37 / 63; or
[0076] -Between 25 / 75 and 35 / 65.
[0077] The diamine component (A) preferably does not contain hexamethylenediamine. The diamine component (A) preferably does not contain bis(aminoalkyl)cyclohexanediamine (such as 1,3-bis(aminomethyl)cyclohexane or 1,4-bis(aminomethyl)cyclohexane). The diamine component (A) preferably does not contain 2-methyl-1,8-octanediamine.
[0078] Dicarboxylic acid component (B)
[0079] The dicarboxylic acid component (B) comprises: between 70.0 and 95.0 mol.% of terephthalic acid and between 5.0 (excluding this value) and 30.0 mol.% of another diacid (DI) selected from the group consisting of: isophthalic acid, adipic acid (AA), azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, 1,4-cyclohexanedicarboxylic acid (CHDA) and mixtures thereof, these proportions in mol % being based on the total amount of diacids in the dicarboxylic acid component (B).
[0080] If the further diacid (DI) has more than 8 carbon atoms, the proportion of the further diacid (DI) is preferably below 20.0 mol %, more preferably below 15.0 mol %.
[0081] If the further diacid (DI) is such that it contains greater than or equal to 8 carbon atoms, the proportion of the further diacid is preferably lower than or equal to 20.0 mol %, more preferably lower than or equal to 15.0 mol %.
[0082] The other diacid (DI) may more particularly be chosen from the group consisting of isophthalic acid, adipic acid (AA), 1,4-cyclohexanedicarboxylic acid (CHDA) and a combination of two or more of said diacids.
[0083] The further diacid (DI) may be one of the diacids listed in Table I. Thus, the further diacid (DI) may be isophthalic acid or adipic acid (AA) or 1,4-cyclohexanedicarboxylic acid (CHDA). The further diacid (DI) is preferably isophthalic acid.
[0084] The proportion of terephthalic acid in the dicarboxylic acid component (B) may preferably be at least 80.0 mol%, preferably at least 83.0 mol%, more preferably at least 85.0 mol%. The proportion may also be at least 87.0 mol%.
[0085] The proportion of the further diacid (DI) in the dicarboxylic acid component (B) is strictly higher than (>) 5.0 mol%. The proportion of the further diacid (DI) in the dicarboxylic acid component (B) is preferably at most 20.0 mol%, preferably at most 17.0 mol%, more preferably at most 15.0 mol%. The proportion can also be at most 13.0 mol%. It can be noted that the further diacid (DI) can be a combination of two diacids, so that the ratios given here correspond to the total proportions of the diacids (DI).
[0086] All these proportions (in mol %) of terephthalic acid and the further diacid (DI) are based on the total amount of diacids in the dicarboxylic acid component (B).
[0087] According to an embodiment, the dicarboxylic acid component (B) consists essentially of or consists of terephthalic acid and the further diacid (DI). The expression "consists essentially of" means that in the context of the present invention in relation to the dicarboxylic acid component (B), the dicarboxylic acid component (B) comprises terephthalic acid and the further diacid (DI) and may also comprise up to 2.0 mol%, preferably up to 1.0 mol%, even more preferably up to 0.5 mol% of diacids other than terephthalic acid and other than DI, the proportion in mol% being based on the total amount of diacids in the dicarboxylic acid component (B). In other words, the dicarboxylic acid component (B) consists of terephthalic acid, the further diacid (DI) and up to 2.0 mol%, preferably up to 1.0 mol%, even more preferably up to 0.5 mol% of at least one diacid other than terephthalic acid and other than DI, the proportion in mol% being based on the total amount of diacids in the dicarboxylic acid component (B).
[0088] The skilled person understands that the polycondensation of the above defined monomers produces a system comprising repeating units (R PA1 ) and (R PA2 ) of polyamide (PA),
[0089]
[0090]
[0091] wherein R1 is a divalent radical derived from DA1 or DA2, and R2 is a divalent radical derived from a diacid (DI). For example, if the diacid (DI) is isophthalic acid, then (R PA2 ) is represented by the following formula:
[0092]
[0093] Therefore, the present invention also relates to a polyamide (PA) comprising recurring units (R) having the following ratios relative to the total amount of recurring units in the polyamide (PA):PA1 ) and (R PA2 ):
[0094] - between 70.0 and 95.0 mol.% (R PA1 );
[0095] - between 5.0 (excluding this value) and 30.0 mol.% (R PA2 );
[0096] in:
[0097] - R1 is a divalent group of a diamine corresponding to the combination of:
[0098] a) a first diamine (DA1) as defined above; and
[0099] b) a second diamine (DA2) as defined above;
[0100] The molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is as defined herein;
[0101] -R2 is a divalent radical of a diacid (DI).
[0102] Repeating unit (R PA1 ) and (R PA2 ) is at least 95.0 mol%. The proportion is preferably at least 99.0 mol%, or even at least 99.5 mol%.
[0103] The polyamide (PA) preferably comprises no repeating units derived from lactam.The polyamide (PA) preferably comprises no repeating units derived from hexamethylenediamine.
[0104] The polyamide (PA) of the invention preferably comprises no repeating units derived from hexamethylenediamine or from bis(aminoalkyl)cyclohexanediamine, such as 1,3-bis(aminomethyl)cyclohexane or 1,4-bis(aminomethyl)cyclohexane, or from 2-methyl-1,8-octanediamine.
[0105] According to a preferred embodiment, the repeating unit (R PA ) is basically composed of repeating units (R PA1 ) and (R PA2 ) is composed of or consists of.
[0106] Repeating unit (R PA1 )
[0107] The skilled person understands that all details and examples relating to the ratio of terephthalic acid and diacid (DI) in the dicarboxylic acid component (B) provided herein can be expressed in terms of repeating units (R PA1 ) and (RPA2 ) are converted in the corresponding proportion.
[0108] Repeating unit (R PA1 ) is between 70.0 and 95.0 mol%. The proportion is preferably at least 80.0 mol%, preferably at least 83.0 mol%, more preferably at least 85.0 mol%. The proportion can also be at least 87.0 mol%.
[0109] Repeating unit (R PA2 )
[0110] Repeating unit (R PA2 ) is between 5.0 (excluding this value) and 30.0 mol%. The proportion is preferably at most 20.0 mol%, preferably at most 17.0 mol%, more preferably at most 15.0 mol%. The proportion can also be at most 13.0 mol%.
[0111] If the polyamide (PA) is based on a diacid having more than 8 carbon atoms, (R PA2 ) is preferably less than 20.0 mol%, more preferably less than 15.0 mol%.
[0112] Number average molecular weight (Mn)
[0113] The polyamide (PA) of the present invention typically has a number average molecular weight ("Mn") ranging from 1,000 g / mol to 40,000 g / mol, for example, from 2,000 g / mol to 35,000 g / mol, from 4,000 to 30,000 g / mol, or from 5,000 g / mol to 20,000 g / mol. Mn can be determined using the following equation (1): Mn = 2,000,000 / [EG] (1), where [EG] is the proportion of end groups in the PA (expressed in mmol / kg), more precisely using known methods for measuring the concentration of amine end groups and acid end groups. The end groups in the polyamide (PA) are typically amine and / or acid moieties. However, when the polycondensation involves the addition of an end-capping agent, the amine end groups are partially or fully converted into one or more modified end groups. For example, when the end cap is an acid such as benzoic acid or acetic acid, the remaining amine groups can be fully or partially converted to amide end groups such as benzamide or acetamide, and these end groups can be easily converted to amide end groups by 1 H NMR for quantification.
[0114] Inherent viscosity (IV)
[0115] The polyamide (PA) preferably exhibits an intrinsic viscosity (IV) between 0.50 and 1.70 dL / g.
[0116] The IV of the polyamide (PA) may more particularly be between 0.70 and 1.00 dL / g or between 0.80 and 1.00 dL / g. The IV of the polyamide (PA) may also more particularly be between 1.00 and 1.50 dL / g or between 1.05 and 1.25 dL / g.
[0117] In the present disclosure, the intrinsic viscosity IV is measured according to ASTM D5336-22 using a phenol / trichloroethylene mixture (60 / 40 weight ratio).
[0118] End Group
[0119] The end groups in the polyamide (PA) are selected from the group of -NH2, -COOH and amide end groups. In fact, the end groups in the polyamide (PA) can be -NH2 or -COOH. However, when the polycondensation involves the addition of an end-capping agent, these end groups can be partially or completely converted into amide end groups.
[0120] The amide end groups are of the formula -NH-C(=O)-R, wherein R is an alkyl, aryl or cycloalkyl group, and / or of the formula -C(=O)-NH-R', wherein R' is an alkyl or cycloalkyl group. R is more particularly a linear or branched C1-C 18 Alkyl or C5-C 10 R' is more particularly a linear or branched C2-C 18 alkyl.
[0121] The amide end group having the formula -NH-C(=O)-R is produced by the reaction of the end group -NH2 with a monocarboxylic acid having the formula R-COOH (capping agent).
[0122] The monocarboxylic acid (capping agent) may advantageously be selected from the group consisting of: benzoic acid; cyclohexanoic acid; R-COOH, wherein R is a linear or branched C2-C 18 and combinations of two or more of these acids. R is a group derived from an acid having the formula R-COOH.
[0123] The monocarboxylic acid (capping agent) may more particularly be chosen from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, lauric acid, stearic acid, 2-ethylhexanoic acid, cyclohexanoic acid, benzoic acid and combinations of two or more of these acids.
[0124] The monocarboxylic acid (capping agent) is more particularly a carboxylic acid having the formula CH3-(CH2) n -COOH, wherein n is an integer between 0 and 16. The amide end group is of the formula -NH-C(=O)-(CH2) n -CH3.
[0125] An amide end group of formula -C(=O)-NH-R' results from the reaction of a terminal group -COOH with a primary amine of formula R'-NH2 (capping agent).
[0126] The primary amine (capping agent) may advantageously be selected from the group consisting of: an amine having the formula R'-NH2, wherein R' is a linear or branched C2-C 18 Alkyl. R' is a group derived from an amine having the formula R'-NH2.
[0127] The primary amine (capping agent) is more particularly a amine having the formula CH3-(CH2) n′ -NH2, wherein n' is an integer between 2 and 18. The amide end group is of the formula -C(=O)-NH-(CH2) n′ -CH3.
[0128] The primary amine (capping agent) may more particularly be chosen from the group consisting of propylamine, butylamine, pentylamine, hexylamine, 2-ethylhexylamine, n-octylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, stearylamine, cyclohexylamine and combinations of two or more of these amines.
[0129] The polyamide (PA) may contain a chain limiter, which is a monofunctional molecule capable of reacting with an amine or carboxylic acid moiety. The chain limiter may more particularly be acetic acid, propionic acid, benzoic acid and / or C6-C 12 Monoalkylamine.
[0130] The ratio of end groups can be determined by 1 H NMR or quantified by potentiometry techniques.
[0131] Biocontent
[0132] The polyamide (PA) typically exhibits a biocontent expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22 of at least 30.0%, preferably at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 36.0%, even more preferably at least 37.0%, even more preferably at least 38.0%, even more preferably at least 39.0%, even more preferably at least 40.0%, more preferably at least 45.0%.
[0133] Biocontent is defined as the % of organic carbon from renewable sources. It corresponds to the 14 The C percentage is the amount of C calculated and corrected for the isotope fraction.
[0134] Both the C9 and C10 diamines can be bio-based or derived from petroleum or natural gas.
[0135]
[0136] The polyamide (PA) disclosed herein is prepared from bio-based 1,9-nonanediamine (C9) and / or 1,10-decanediamine (C10). This makes it possible to obtain polyamide (PA) with a high bio-content.
[0137] According to an embodiment, the polyamide (PA) disclosed herein is prepared from bio-based 1,9-nonanediamine (C9) and / or 1,10-decanediamine (C10) exhibiting a biocontent of at least 99.0%, preferably at least 99.5%, preferably at least 99.9%, the biocontent being expressed as % of organic carbon from renewable sources measured according to ASTM D6866-22.
[0138] The biocontent can also be increased by using bio-based terephthalic acid. The biocontent as defined above can then be at least 75.0%, or even at least 79.0%. Bio-based terephthalic acid can be prepared, for example, from bio-based furfural as disclosed in the following document: Tachibana, Y., Kimura, S. & Kasuya, K.-i. "Synthesis and Verification of Biobased Terephthalic Acid from Furfural" Sci. Rep. [Science Report] 5, 8249; DOI: 10.1038 / srep08249 (2015).
[0139] Hygroscopicity and water aging resistance
[0140] The polyamide (PA) of the present invention advantageously exhibits a water absorption at 23° C. of less than 5.0 wt.%. The water absorption at 23° C. is determined by (i) providing a test specimen formed according to ISO 527 in its dry state (moisture content less than 0.2 wt.%), (ii) immersing the test specimen in deionized water at 23° C. until constant weight is reached, (iii) calculating the water absorption using the following formula:
[0141]
[0142] Where W 之前 is the weight of the molded specimen in its initial dry state and W 之后 It is the weight of the molded specimen after water absorption.
[0143] The polyamide (PA) of the present invention also exhibits hot water resistance as disclosed below. The test is performed by placing the sample in hot water at 135°C in a closed container for 200 hours.
[0144] The polyamide (PA) of the present invention advantageously exhibits a water absorption of less than 5.0% (≤ 5.0%) at 135°C for 200 hours. The water absorption at 135°C for 200 hours is determined by a method comprising the following steps: (i) providing three samples in the form of ISO527 IA type tensile bars in their dry state (water content less than 0.2 wt.%), (ii) immersing the three samples in deionized water at 135°C for 200 hours, (iii) determining the water absorption for each sample using the following formula:
[0145]
[0146] Where W 之前 is the weight of the sample in its initial dry state, and W 之后 is the weight of the sample at the end of step (ii); (iv) the water absorption is calculated as the arithmetic mean of the three water absorptions determined for the three samples.
[0147] The polyamide (PA) of the present invention advantageously exhibits an IV retention of at least 90.0%, preferably at least 95.0%. The IV retention is determined by a method comprising the following steps: (i) providing a sample formed in the form of an ISO527 IA type tensile bar in its dry state (moisture content less than 0.2 wt.%), (ii) immersing the sample in deionized water at 135° C. for 200 hours, (iii) determining the IV retention of the sample using the following formula:
[0148] IV Retention Rate = IV 之后 / IV 之前 ×100
[0149] IV 之前 and IV 之后 is the intrinsic viscosity of the sample before and after testing.
[0150] Thermal properties of polyamide (PA)
[0151] As indicated above, it has surprisingly been found that the polyamide (PA) of the present invention exhibits a combination of thermal properties, as described in detail below.
[0152] 1) Melting point (Tm)
[0153] The polyamide exhibits a Tm of at least 238° C., preferably at least 240° C. The Tm may preferably be at least 250° C., preferably at least 260° C.
[0154] The Tm may be at least 265°C or even at least 270°C.
[0155] Tm is typically at most 300°C or at most 290°C.
[0156] The Tm is preferably strictly below 290°C (<290°C).
[0157] The Tm may also be up to 280°C.
[0158] The Tm may be between 238°C and 300°C or between 240°C and 300°C.
[0159] The Tm may also be between 238°C and 280°C.
[0160] Tm can be measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using heating and cooling rates of 20°C / min.
[0161] Tm can be measured by differential scanning calorimetry ("DSC") according to ASTM D3418 using a heating and cooling rate of 20°C / min. Three scans are used for each DSC test: a first heating to 350°C, followed by a first cooling to 0°C, followed by a second heating to 360°C. Tm is determined from the second heating.
[0162] Tm can more particularly be measured by the method as described in the experimental part.
[0163] 2) Heat of Melting (Hm)
[0164] Polyamide (PA) is semi-crystalline.
[0165] The polyamide (PA) exhibits a heat of fusion (Hm) of at least 30.0 J / g, preferably at least 35.0 J / g.
[0166] Hm may be at most 90.0 J / g or at most 80.0 J / g.
[0167] Hm may be between 30.0 J / g and 90.0 J / g.
[0168] Hm can be measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using heating and cooling rates of 20°C / min.
[0169] Hm can be measured by differential scanning calorimetry ("DSC") according to ASTM D3418 using a heating and cooling rate of 20°C / min. Three scans are used for each DSC test: a first heating to 350°C, followed by a first cooling to 0°C, followed by a second heating to 360°C.
[0170] Hm can more particularly be measured by the method as described in the experimental part.
[0171] 3) Glass transition temperature (Tg)
[0172] The polyamide exhibits a Tg of at least 100° C. The Tg of the polyamide (PA) may preferably be at least 105° C., preferably at least 110° C., preferably at least 115° C., preferably at least 120° C.
[0173] Polyamide (PA) typically exhibits a Tg of up to 140°C.
[0174] The Tg may more particularly be between 100°C and 135°C.
[0175] Tg can be measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using heating and cooling rates of 20°C / min.
[0176] Tg can be measured by differential scanning calorimetry ("DSC") according to ASTM D3418 using a heating and cooling rate of 20°C / min. Three scans are used for each DSC test: a first heating to 350°C, followed by a first cooling to 0°C, followed by a second heating to 360°C. Tg is determined from the second heating.
[0177] Tg can more particularly be measured by the method as described in the experimental part.
[0178] As detailed above, the polyamide (PA) of the present invention exhibits a combination of thermal properties. Therefore, the present invention more particularly relates to a polyamide (PA) which exhibits the following combination of properties:
[0179] - a Tm between 240° C. and 300° C., preferably between 240° C. and 290° C. (excluding the 290° C. value);
[0180] - a Tg of at least 115°C, preferably at least 120°C;
[0181] - A biocontent of at least 30.0%, preferably at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%, even more preferably at least 40.0%, even more preferably at least 45.0%.
[0182] The invention also relates more particularly to a polyamide (PA) which exhibits the following combination of properties:
[0183] - Tm between 240°C and 300°C;
[0184] - Tg of at least 120°C;
[0185] - A biocontent of at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%, even more preferably at least 40.0%, more preferably at least 45.0%.
[0186] 4) Tm / Tg ratio
[0187] As mentioned above, polyamide (PA) exhibits a combination of thermal properties, and for a given Tg, it is beneficial to have a limited Tm. Therefore, Tm / Tg is preferably limited by the inequality of equation 1 (eq. 1), preferably equation 2 (eq. 2):
[0188] Tm / Tg<-0.0372×Tg(in °C)+6.8402(eq.1)
[0189] Tm / Tg<-0.0372×Tg (in °C)+6.8002 (eq. 2).
[0190] The copolyamides of D1 (Table I) do not obey either of these two inequalities.
[0191] Example (E*)
[0192] According to a preferred embodiment (E*), the present invention relates to a polyamide (PA*) whose repeating units (R PA *) is formed by the polycondensation of a diamine component (A) and a dicarboxylic acid component (B), wherein:
[0193] - the diamine component (A) comprises, consists essentially of, or consists of:
[0194] a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and
[0195] b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof;
[0196] wherein the proportion of the second diamine (DA2) in the diamine component (A) is between 60.0 and 85.0 mol %, and the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 15 / 85 and 40 / 60;
[0197] - the dicarboxylic acid component (B) comprises, consists essentially of or consists of:
[0198] a) between 82.0 and 94.0 mol.% of terephthalic acid;
[0199] b) between 6.0 and 18.0 mol.% of isophthalic acid;
[0200] These proportions in mol % are based on the total amount of diacids in the dicarboxylic acid component (B);
[0201] And exhibit the following characteristics:
[0202] - a Tm between 240°C and 290°C (excluding the 290°C value);
[0203] - Tg between 115°C and 135°C;
[0204] - Optionally a biocontent of at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%.
[0205] The present invention also relates to a polyamide (PA*) whose recurring units consist essentially of recurring units (R) having the following ratios relative to the total amount of recurring units in the polyamide (PA): PA1 ) and (R PA2 ) consists of or is composed of:
[0206] - between 82.0 and 94.0 mol.% (R PA1 )
[0207]
[0208] - between 6.0 and 18.0 mol.% (R PA2 )
[0209]
[0210] in:
[0211] - R1 is a divalent group of a diamine corresponding to the combination of:
[0212] a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and
[0213] b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof;
[0214] The molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 15 / 85 and 40 / 60;
[0215] wherein the proportion of repeating units derived from DA2 is between 60.0 and 85.0 mol %;
[0216] And exhibit the following characteristics:
[0217] - a Tm between 240°C and 290°C (excluding the 290°C value);
[0218] - Tg between 115°C and 135°C;
[0219] - Optionally a biocontent of at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%.
[0220] The proportion of isophthalic acid in the dicarboxylic acid component (B) or the repeating units (R PA2 ) may more particularly be between 8.0 and 17.0 mol % or between 8.0 and 12.0 mol %.
[0221] The polyamide (PA) and repeating unit (R PA All embodiments, details and characteristics of ) apply to polyamide (PA*) and repeating units (R PA* ).
[0222] Process for preparing polyamide (PA) and (PA*)
[0223] The polyamides (PA) and (PA*) described herein can be prepared by any conventional process suitable for the synthesis of polyamides and polyphthalamides. The following details relate to polyamide (PA), but are of course applicable to polyamide (PA*).
[0224] Polyamides (PA) are usually produced by polycondensation in the melt.
[0225] The polyamide (PA) can be prepared by heating a reaction mixture (RM) comprising or consisting of all monomers (DA1, DA2, terephthalic acid and DI) in the presence of less than 60 wt.%, preferably less than 30 wt.%, preferably less than 20 wt.%, preferably less than 10 wt.% of water, preferably without adding water.
[0226] As is well known in polycondensation, the reaction mixture comprises an amount of the above-mentioned diamine and diacid such that the ratio of -COOH groups from the diacid and the ratio of -NH2 groups from the diamine are substantially equimolar. The ratio amine / acid may be comprised between 0.9 and 1.1, preferentially between 0.95 and 1.05, even more preferentially between 0.98 and 1.02.
[0227] The reaction mixture (RM) preferably comprises a catalyst. The catalyst may be selected from the group consisting of phosphorous acid, orthophosphoric acid, metaphosphoric acid, alkali metal hypophosphites (such as sodium hypophosphite) and phenylphosphinic acid. A convenient catalyst used is phosphorous acid.
[0228] For the purpose of controlling the molar mass, the reaction mixture (RM) may also further comprise at least one chain limiter (capping agent) as disclosed above.
[0229] The temperature at which the reaction mixture (RM) is heated must be high enough to initiate the reaction between the amine groups of the diamine component (A) and the carboxyl groups of the dicarboxylic acid component (B) and to reduce the viscosity of the mixture. The temperature is generally at least 150° C., preferably at least 200° C. The polycondensation leads to the formation of amide bonds and the release of water as a by-product.
[0230] The temperature can be increased stepwise during the polycondensation. An example of a stepwise increase is given for Example 1 and can be followed for the preparation of polyamide (PA).
[0231] The polycondensation is advantageously carried out in a well-stirred vessel equipped with a device for removing the volatile products of the reaction. As the viscosity of the reaction mixture increases over time, the agitator is suitable for providing sufficient agitation for the reaction mixture at the beginning of the polymerization and when the polycondensation conversion is near completion.
[0232] The conditions disclosed in the experimental part can be conveniently used to prepare polyamide (PA).
[0233] Thermoplastic Composites (TPC)
[0234] Polyamide (PA) or (PA*) is suitable for use in the preparation of thermoplastic composites (TPC). The following details refer to polyamide (PA), but are applicable to polyamide (PA*).
[0235] The thermoplastic composite (TPC) comprises:
[0236] a polymer matrix comprising or consisting of: (i) a polyamide (PA) or (PA*) and (ii) optionally at least one plastic additive; and
[0237] - Fibers embedded in the polymer matrix.
[0238] The thermoplastic composite material comprises a polymer matrix and fibers. The fibers are preferably bonded or cohesively bonded to the matrix, which generally completely surrounds the fibers. The function of the fibers held in place by the polymer matrix is to provide improved mechanical properties while minimizing the weight of the composite material.
[0239] Typically, the proportion of fibres is at least 5.0 wt %, this proportion being given relative to the weight of the thermoplastic composite material.
[0240] The polymer matrix comprises or consists of: (i) the polyamide (PA) of the present invention and (ii) optionally at least one plastic additive, which is usually and preferably blended with the polyamide (PA). The plastic additive may be selected from the group consisting of: colorants (e.g. dyes and / or pigments), UV stabilizers, heat stabilizers, antioxidants, acid scavengers, processing aids, internal and / or external lubricants, flame retardants, smoke suppressants, antistatic agents, anti-caking agents and any combination thereof. The proportion of the one or more plastic additives in the polymer matrix is usually less than 20.0 wt%, based on the total weight of the polymer matrix.
[0241] Fibers generally exhibit high specific stiffness and strength values.
[0242] The fibers may be of inorganic type (eg glass fibers) or of organic type (eg aramid fibers or carbon fibers). It is also possible to use combinations of various fibers.
[0243] The fibers may be selected from the group consisting of glass fibers, carbon fibers, aramid fibers, stainless steel fibers, potassium titanate whiskers, and combinations of two or more thereof.
[0244] The thermoplastic composite material is prepared by any of the techniques known to the skilled person, in particular as disclosed in Composites Manufacturing 1992, Vol. 3, No. 4 "Impregnation technology for thermoplastic matrix composites". These techniques are based on a first step of contacting the polymer composition (C), in particular in powder form, with the fibers and a second step of applying heat and pressure to the product obtained at the end of step a). The impregnation technique disclosed in US Pat. No. 5,236,972 may be followed.
[0245] In step a), the thermoplastic composition is preferably homogeneous and homogeneously distributed around the fibers, especially in an amount that reduces the porosity in the final thermoplastic composite. A Tm in the range of 240-300°C, preferably 240-290°C (exclusive) is recommended for this purpose.
[0246] Applications of Thermoplastic Composites (TPC)
[0247] The thermoplastic composites (TPCs) disclosed herein can be used to prepare articles for the automotive industry.
[0248] [Experimental part]
[0249] The examples of the present invention illustrate the synthesis, thermal properties and mechanical properties of polyamides. The raw materials used to form the samples are provided below:
[0250] Raw materials used
[0251] The following raw materials were used to prepare the polymer samples: 1,9-diaminononane (produced at Solvay and derived from bio-based oleic acid, purity > 98.0%), 1,10-diaminodecane (produced at Solvay and derived from bio-based castor oil, purity > 98.0%), terephthalic acid (from Flint Hills Resources), isophthalic acid (from Flint Hills Resources), 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof (from Evonik Industries), adipic acid (from Ascend Performance Materials), 1,4-cyclohexanedicarboxylic acid (from Sigma-Aldrich), and 1,4-diaminooctane (from Sigma-Aldrich). Aldrich)) and phosphoric acid (from Sigma-Aldrich).
[0252] Preparation of polyamide
[0253] All copolyamides disclosed in Table I were prepared by polycondensation in an autoclave reactor equipped with a distillate line equipped with a pressure control valve. All copolyamides of Table II were prepared following the procedure detailed below for Example 1 (except for the compositions).
[0254] Example 1
[0255] The polyamide of Example 1 was prepared by charging a reactor with 4.89 g of 1,9-diaminononane, 0.64 g of a mixture of 2,2,4-trimethyl-1,6-hexanediamine and 2,4,4-trimethyl-1,6-hexanediamine, 5.02 g of terephthalic acid, 0.56 g of isophthalic acid, 5.48 g of deionized water, and 0.0037 g of phosphoric acid. The reactor was sealed and purged three times with N2 gas. The reactor was heated to 177°C and held for 25 min, then heated to 232°C and held for 25 min, then heated to 288°C and held for 25 min, then heated to 321°C and held for 15 min. The generated steam was slowly released to keep the internal pressure below 200 psig. Once the temperature was at 321°C for 15 min, the reactor pressure was slowly reduced to atmospheric pressure over 30 min. While the decompression was being carried out for 15 min, the reactor was cooled to 302°C. After maintaining at 302° C. for another 15 min and completing the decompression, the reactor was continuously purged with N 2 gas for 25 min. Afterwards, the reactor was cooled to RT and the polymer was taken out of the reactor.
[0256] Thermal properties
[0257] Tg, Tm and Hm are measured by differential scanning calorimetry ("DSC") according to ASTM D3418 using a heating and cooling rate of 20°C / min. Three scans are used for each DSC test: a first heating to 350°C, followed by a first cooling to 0°C, followed by a second heating to 360°C. Tg, Tm and Hm are determined from the second heating.
[0258] All polyamides in Examples E1 to E12 except E1, E3 and E5 obey the inequalities of Eq. 1 and Eq. 2.
[0259]
[0260]
[0261] Table III
[0262]
[0263] *Measured according to ISO527
[0264] **Measured according to the protocol defined in the instructions (see §"Moisture absorption and water aging resistance")
Claims
1. A polyamide (PA) comprising repeating units (R) formed by polycondensation of a diamine component (A) and a dicarboxylic acid component (B) PA ),in: - The diamine component (A) comprises: a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof; wherein the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 5 / 95 and 47 / 53; and wherein the proportion of DA2 in the diamine component (A) is greater than or equal to 53.0 mol % (≥53.0 mol %), the proportion being based on the total amount of diamines in the diamine component (A); - The dicarboxylic acid component (B) comprises: c) between 70.0 and 95.0 mol.% of terephthalic acid; d) between 5.0 (excluding this value) and 30.0 mol.% of another diacid (DI) selected from the group consisting of isophthalic acid, adipic acid (AA), azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, 1,4-cyclohexanedicarboxylic acid (CHDA) and mixtures thereof; These proportions in mol % are based on the total amount of dicarboxylic acids in the dicarboxylic acid component (B).
2. The polyamide (PA) according to claim 1, wherein The diamine component (A) consists essentially of or consists of the first diamine (DA1) and the second diamine (DA2).
3. The polyamide (PA) according to claim 1 or 2, wherein The diamine component (A) consists of the first diamine (DA1), the second diamine (DA2) and up to 2.0 mol %, preferably up to 1.0 mol %, even more preferably up to 0.5 mol % of at least one diamine other than DA1 and DA2, the proportion in mol % being based on the total amount of diamines in the diamine component (A).
4. The polyamide (PA) according to any one of the preceding claims, wherein The dicarboxylic acid component (B) consists essentially of or consists of terephthalic acid and the further diacid (DI).
5. The polyamide (PA) according to any one of claims 1 to 4, wherein The dicarboxylic acid component (B) consists of terephthalic acid, the further diacid (DI) and up to 2.0 mol %, preferably up to 1.0 mol %, even more preferably up to 0.5 mol %, of at least one diacid other than terephthalic acid and other than DI, the proportions in mol % being based on the total amount of diacids in the dicarboxylic acid component (B).
6. The polyamide (PA) according to any one of the preceding claims, wherein If the diamine component (A) contains 2-methyl-1,8-octanediamine (MODA), the proportion of MODA in the diamine component (A) is lower than and equal to 10.0 mol % (≤10.0 mol %), preferably lower than and equal to 5.0 mol % (≤5.0 mol %), the proportion in mol % being based on the total amount of diamines in the diamine component (A).
7. A polyamide (PA) comprising repeating units (R) formed by polycondensation of a diamine component (A) and a dicarboxylic acid component (B). PA ),in: - The diamine component (A) consists essentially of or consists of: a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof; wherein the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 5 / 95 and 47 / 53; - the dicarboxylic acid component (B) consists essentially of or consists of: c) between 70.0 and 95.0 mol.% of terephthalic acid; d) between 5.0 (excluding this value) and 30.0 mol.% of another diacid (DI) selected from the group consisting of isophthalic acid, adipic acid (AA), azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, 1,4-cyclohexanedicarboxylic acid (CHDA) and mixtures thereof; These proportions in mol % are based on the total amount of dicarboxylic acids in the dicarboxylic acid component (B).
8. A polyamide (PA), in particular a polyamide (PA) according to any one of the preceding claims, comprising repeating units (R PA1 ) and (R PA2 ), The ratios of these repeating units are as follows: - between 70.0 and 95.0 mol.% (R PA1 ); - between 5.0 (excluding this value) and 30.0 mol.% (R PA2 ); in: - R1 is a divalent group of a diamine corresponding to the combination of: a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof; The molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 5 / 95 and 47 / 53; - R2 is a divalent radical of a diacid (DI) selected from the group consisting of isophthalic acid, adipic acid (AA), azelaic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, 1,4-cyclohexanedicarboxylic acid (CHDA), and mixtures thereof.
9. The polyamide (PA) according to claim 8, wherein Repeating unit (R PA1 ) and (R PA2 ) is at least 95.0 mol%, preferably at least 99.0 mol%, more preferably at least 99.5 mol%.
10. The polyamide (PA) according to claim 8, wherein The repeating units of the polyamide (PA) consist essentially of repeating units (R PA1 ) and (R PA2 ) is composed of or consists of.
11. The polyamide according to any one of claims 1 to 7, wherein The repeating units of the polyamide (PA) consist essentially of repeating units (R PA ) is composed of or consists of.
12. The polyamide (PA) according to any one of the preceding claims, wherein The diacid (DI) is selected from the group consisting of isophthalic acid, adipic acid (AA), 1,4-cyclohexanedicarboxylic acid (CHDA) and a combination of two or more of said diacids; preferably, the diacid (DI) is isophthalic acid.
13. The polyamide (PA) according to any one of the preceding claims, wherein The molar ratio DA1 / DA2 is: - between 5 / 95 and 40 / 60; or - between 15 / 85 and 47 / 53; or - between 15 / 85 and 37 / 63; or - between 18 / 82 and 47 / 53; or - between 8 / 92 and 37 / 63; or -Between 25 / 75 and 35 / 65.
14. The polyamide (PA) according to any one of the preceding claims, wherein The proportion of terephthalic acid in the dicarboxylic acid component (B) or the repeating units (R PA1 ) is at least 80.0 mol %, preferably at least 83.0 mol %, preferably at least 85.0 mol %.
15. The polyamide (PA) according to any one of the preceding claims, wherein The proportion of terephthalic acid in the dicarboxylic acid component (B) or the repeating units (R PA1 ) is at least 87.0 mol%.
16. The polyamide (PA) according to any one of the preceding claims, wherein The proportion of the diacid (DI) other than terephthalic acid in the dicarboxylic acid component (B) or the repeating units (R PA2 ) is at most 20.0 mol %, preferably at most 17.0 mol %, preferably at most 15.0 mol %.
17. The polyamide (PA) according to any one of the preceding claims, wherein The proportion of the diacid (DI) other than terephthalic acid in the dicarboxylic acid component (B) or the repeating units (R PA2 ) is at most 13.0 mol%.
18. A polyamide (PA), in particular a polyamide (PA) according to any one of the preceding claims, wherein the repeating units (R PA *) is formed by the polycondensation of a diamine component (A) and a dicarboxylic acid component (B), wherein: - the diamine component (A) comprises, consists essentially of, or consists of: a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof; wherein the proportion of the second diamine (DA2) in the diamine component (A) is between 60.0 and 85.0 mol %, and the molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 15 / 85 and 40 / 60; - the dicarboxylic acid component (B) comprises, consists essentially of or consists of: a) between 82.0 and 94.0 mol.% of terephthalic acid; b) between 6.0 and 18.0 mol.% of isophthalic acid; These proportions in mol % are based on the total amount of diacids in the dicarboxylic acid component (B); And exhibit the following characteristics: - a melting point Tm between 240° C. and 290° C. (excluding the 290° C. value); - a glass transition temperature Tg between 115° C. and 135° C.; Tm and Tg are measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using a heating and cooling rate of 20°C / min; - Optionally a biocontent of at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%, expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22.
19. A polyamide (PA), in particular a polyamide (PA) according to any one of the preceding claims, the recurring units of which consist essentially of recurring units (R PA1 ) and (R PA2 ) consists of or is composed of: - between 82.0 and 94.0 mol.% (R PA1 ) - between 6.0 and 18.0 mol.% (R PA2 ) in: - R1 is a divalent group of a diamine corresponding to the combination of: a) a first diamine (DA1) selected from the group consisting of 2,2,4-trimethyl-1,6-hexanediamine (2,2,4-TMD), 2,4,4-trimethyl-1,6-hexanediamine (2,4,4-TMD) and mixtures thereof; and b) a second diamine (DA2) selected from the group consisting of 1,9-nonanediamine (C9), 1,10-decanediamine (C10), and mixtures thereof; The molar ratio DA1 / DA2 of the first diamine (DA1) to the second diamine (DA2) is between 15 / 85 and 40 / 60; wherein the proportion of repeating units derived from DA2 is between 60.0 and 85.0 mol %; And exhibit the following characteristics: - a melting point Tm between 240° C. and 290° C. (excluding the 290° C. value); - a glass transition temperature Tg between 115° C. and 135° C.; Tm and Tg are measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using a heating and cooling rate of 20°C / min; - Optionally a biocontent of at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%, expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22.
20. The polyamide (PA) according to any of the preceding claims, exhibiting a biocontent expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22, of at least 30.0%, preferably at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 36.0%, even more preferably at least 37.0%, even more preferably at least 38.0%, even more preferably at least 39.0%, even more preferably at least 40.0%, more preferably at least 45.0%.
21. The polyamide (PA) according to any one of the preceding claims, prepared from bio-based 1,9-nonanediamine (C9) and / or 1,10-decanediamine (C10), in particular prepared from bio-based 1,9-nonanediamine (C9) and / or 1,10-decanediamine (C10) exhibiting a biocontent of at least 99.0%, preferably at least 99.5%, preferably at least 99.9%, expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22.
22. The polyamide (PA) according to any one of the preceding claims, exhibiting a melting point Tm of at least 238°C, preferably at least 240°C, preferably at least 250°C or at least 260°C, Tm being measured by differential scanning calorimetry ("DSC") according to ASTM D3418, in particular using a heating and cooling rate of 20°C / min.
23. The polyamide (PA) according to any one of the preceding claims, exhibiting a melting point Tm of at most 300°C or at most 290°C, Tm being measured by differential scanning calorimetry ("DSC") according to ASTM D3418, in particular using a heating and cooling rate of 20°C / min.
24. The polyamide (PA) according to any one of the preceding claims, exhibiting a melting point Tm strictly below 290°C (<290°C) or between 238°C and 280°C, Tm being measured by Differential Scanning Calorimetry ("DSC") according to ASTM D3418, in particular using a heating and cooling rate of 20°C / min.
25. The polyamide (PA) according to any one of the preceding claims, wherein The polyamide is semi-crystalline.
26. The polyamide (PA) according to any one of the preceding claims, exhibiting a heat of fusion Hm of at least 30.0 J / g, preferably at least 35.0 J / g, Hm measured by differential scanning calorimetry ("DSC") according to ASTM D3418, in particular using a heating and cooling rate of 20°C / min.
27. The polyamide (PA) according to any one of the preceding claims, exhibiting a glass transition temperature (Tg) of at least 100°C, preferably at least 105°C, preferably at least 110°C, preferably at least 115°C, preferably at least 120°C, Tg being measured by differential scanning calorimetry ("DSC") according to ASTM D3418, in particular using a heating and cooling rate of 20°C / min.
28. The polyamide (PA) according to any one of the preceding claims, which exhibits the following properties: a melting point Tm between 240° C. and 300° C., preferably between 240° C. and 290° C. (excluding the 290° C. value); - a glass transition temperature Tg of at least 115° C., preferably at least 120° C.; Tm and Tg are measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using a heating and cooling rate of 20°C / min; - a biocontent expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22.
29. The polyamide (PA) according to any one of the preceding claims, which exhibits the following properties: - a melting point Tm between 240° C. and 300° C.; - a glass transition temperature Tg of at least 120°C; Tm and Tg are measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using a heating and cooling rate of 20°C / min; - A biocontent expressed as % of organic carbon of renewable origin measured according to ASTM D6866-22 of at least 33.0%, preferably at least 35.0 mol%, even more preferably at least 37.0%, even more preferably at least 40.0%, even more preferably at least 45.0%.
30. The polyamide (PA) according to any one of the preceding claims, which exhibits a melting point Tm and a glass transition temperature Tg that follow the inequality of equation 1 (eq. 1), preferably the inequality of equation 2 (eq. 2): Tm / Tg<-0.0372×Tg(in °C)+6.8402(eq.1) Tm / Tg<-0.0372×Tg (in °C)+6.8002 (eq. 2); Tm and Tg are measured by differential scanning calorimetry ("DSC") according to ASTM D3418, particularly using heating and cooling rates of 20°C / min.
31. The polyamide (PA) according to any one of the preceding claims, wherein The end groups of the polyamide (PA) are selected from the group consisting of -NH2, -COOH and amide end groups, wherein the amide end groups are of the formula -NH-C(=O)-R, wherein R is an alkyl, aryl or cycloalkyl group, and / or of the formula -C(=O)-NH-R', wherein R' is an alkyl or cycloalkyl group.
32. Polyamide (PA) according to any of the preceding claims, exhibiting an intrinsic viscosity (IV) between 0.50 and 1.70 dL / g, measured according to ASTM D5336-22 using a phenol / trichloroethylene mixture (60 / 40 weight ratio).
33. The polyamide (PA) according to claim 32, wherein The IV is: - between 0.70 and 1.00 dL / g; - between 0.80 and 1.00 dL / g; or - between 1.00 and 1.50 dL / g; or - Between 1.05 and 1.25 dL / g.
34. The polyamide (PA) according to any one of the preceding claims, wherein The polyamide (PA) exhibits a water absorption at 135° C. for 200 hours of less than 5.0% (≤5.0%), the water absorption at 135° C. for 200 hours being determined by a method comprising the following steps: (i) providing three samples formed in the form of ISO527 Type IA tensile bars in their dry state (water content less than 0.2 wt.%), (ii) immersing the three samples in deionized water at 135° C. for 200 hours, (iii) determining the water absorption for each sample using the following formula: Where W 之前 is the weight of the sample in its initial dry state, and W 之后 is the weight of the sample at the end of step (ii); and (iv) the water absorption is calculated as the arithmetic mean of the three water absorptions determined for the three samples.
35. The polyamide (PA) according to any one of the preceding claims, wherein The polyamide (PA) exhibits an IV retention of at least 90.0%, preferably at least 95.0%, determined by a method comprising the steps of: (i) providing a sample in its dry state (water content less than 0.2 wt.%) formed in the form of an ISO527 Type IA tensile bar, (ii) immersing the sample in deionized water at 135° C. for 200 hours, (iii) determining the IV retention of the sample using the following formula: IV Retention Rate = IV 之后 / IV 之前 ×100 IV 之前 and IV 之后 is the intrinsic viscosity of the sample before and after testing.
36. The polyamide (PA) according to any one of the preceding claims, wherein DA2 is 1,9-nonanediamine or DA2 is 1,10-decanediamine.
37. The polyamide (PA) according to any one of the preceding claims, wherein The polyamide (PA) comprises no repeating units which are derived from hexamethylenediamine or from bis(aminoalkyl)cyclohexanediamine or from lactams or from amino acids.
38. A process for preparing a polyamide as claimed in any one of the preceding claims, the process consisting of: The reaction mixture (RM) comprising all monomers (DA1, DA2, terephthalic acid and DI) is heated in the presence of less than 60 wt.%, preferably less than 30 wt.%, preferably less than 20 wt.%, preferably less than 10 wt.% of water, preferably without adding water.
39. A thermoplastic composite (TPC), comprising: - a polymer matrix comprising or consisting of: (i) a polyamide (PA) according to any one of claims 1 to 37, and (ii) optionally at least one plastic additive; and - Fibers embedded in the polymer matrix.
40. The thermoplastic composite material according to claim 39, wherein: The fibers are selected from the group consisting of glass fibers, carbon fibers, aramid fibers, stainless steel fibers, potassium titanate whiskers, and combinations of two or more thereof.
Citation Information
Patent Citations
Binder fiber and separator for alkaline cell using same
EP1795632A1
Molding compound on the basis of a copolyamide containing terephthalic acid and trimethylhexamethylene diamine units
US20120095161A1
Polyamide compositions from mixtures of trimethylhexamethylene diamine, hexamethylene diamine and diacids
US4476280A
Crystalline copolyamides from terephthalic acid and hexamethylenediamine and trimethylhexamethylenediamine
US4495328A
Thermoplastic powder slurry for fiber impregnation and film formation
US5236972A